Are hazard models superior to traditional bankruptcy prediction approaches? A comprehensive test - Bauer, Julian; Agarwal, Vineet (Journal of Banking & Finance, 2014)
In recent years hazard models, using both market and accounting information, have become state of the art in predicting firm bankruptcies. However, a comprehensive test comparing their performance against the traditional accounting-based approach or the contingent claims approach is missing in the literature. Using a complete database of UK Main listed firms between 1979 and 2009, our Receiver Operating Characteristics (ROC) curve analysis shows that the hazard models are superior to the alternatives. Further, our information content tests demonstrate that the hazard models subsume all bankruptcy related information in the Taffler (1983) z-score model as well as in Bharath and Shumway (2008) contingent claims-based model. Finally, using a mixed regime competitive loan market with different costs of misclassification, the economic benefit of using the Shumway (2001) hazard model is clear, particularly when the performance is judged with return on risk weighted assets computed under Basel III.